2022
DOI: 10.1111/1556-4029.15036
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community succession of submerged bones in an aquatic habitat

Abstract: After death, microbes (including bacteria and fungi) colonize carrion from a variety of sources during the decomposition process. The predictable succession of microbes could be useful for forensics, such as postmortem submersion interval estimation (PMSI) for aquatic deaths. However, gaps exist in our understanding of microbial succession on submerged bone, particularly regarding longer-term decomposition (>1 year), fungal composition, and differences between internal and external microbial communities.To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In addition, machine learning can be used for PMI estimation in microbial forensics (Johnson et al, 2016 ; Liu et al, 2020 , 2021 ; Cao et al, 2021 ; Cartozzo et al, 2021 ; Randall et al, 2021 ; Zhang et al, 2021 ; Kaszubinski et al, 2022 ; Zhao et al, 2022 ). RF models are widely used for PMI estimation and postmortem submersion interval (PMSI) diagnosis (Metcalf et al, 2013 ; Pechal et al, 2014 ; Cartozzo et al, 2021 ; Randall et al, 2021 ; Zhang et al, 2021 ; Kaszubinski et al, 2022 ; Zhao et al, 2022 ). In 2013, Metcalf et al ( 2013 ) first proposed the concept of a “microbial clock” to infer PMI by setting up regression models using an RF.…”
Section: Applications Of Machine Learning In Forensic Microbiologymentioning
confidence: 99%
“…In addition, machine learning can be used for PMI estimation in microbial forensics (Johnson et al, 2016 ; Liu et al, 2020 , 2021 ; Cao et al, 2021 ; Cartozzo et al, 2021 ; Randall et al, 2021 ; Zhang et al, 2021 ; Kaszubinski et al, 2022 ; Zhao et al, 2022 ). RF models are widely used for PMI estimation and postmortem submersion interval (PMSI) diagnosis (Metcalf et al, 2013 ; Pechal et al, 2014 ; Cartozzo et al, 2021 ; Randall et al, 2021 ; Zhang et al, 2021 ; Kaszubinski et al, 2022 ; Zhao et al, 2022 ). In 2013, Metcalf et al ( 2013 ) first proposed the concept of a “microbial clock” to infer PMI by setting up regression models using an RF.…”
Section: Applications Of Machine Learning In Forensic Microbiologymentioning
confidence: 99%
“…The model using rib microbiota performed best within 353 days, with a root mean square error (RMSE) of ±27 days, while the model using scapula microbiota performed best within 579 days with a RMSE of ±63 days ( Cartozzo et al, 2021 ; Randall et al, 2021 ). Kaszubinski et al (2022) constructed a RF regression model using microbial communities from pig bone within 547 days, and the model exhibited high accuracy, explaining more than 80% of the variation in PMSI. Recently, Liu et al (2020 , 2021) compared the performance of RF, SVM, and ANN models using microbial communities in cecum and concluded that the ANN model performed best, with a MAE of 1.5 ± 0.8 h within 24 h and 14.5 ± 4.4 h within 15 days after death for PMI prediction.…”
Section: Application Of Artificial Intelligence For Pmi Prediction Ba...mentioning
confidence: 99%
“…Although decomposition in aquatic environments has received less study, it is not a rare occurrence in investigations, with a primary focus on detecting the presence of diatoms, algae, and scavenging activity of aquatic species [16][17][18]. Only a few authors have discussed the utility of microbial communities in estimating PMI [16,19,20]. In a study conducted by Cartozzo et al [20], they estimated PMI in freshwater by studying the successional pattern and associated changes in the bacterial community within submerged skeletal remains of pigs.…”
Section: Introductionmentioning
confidence: 99%